The Legitimation of Self-Regulation and Co-Regulation in Corporatist Concepts of Legal Scholars in the Weimar Republic - Collin, Peter (2017)
Corporatist regulation has a hybrid structure in that it covers state regulation, regulated self-regulation as well as private-public co-regulation. Notably diverging from the standard mode of state regulation, such arrangements required a higher degree of legitimation. Corporatist concepts flourished in the Weimar Republic. This paper deals with three legal scholars’ considerations regarding how to legitimize corporatist models, namely Edgar Tatarin-Tarnheyden, Heinrich Herrfahrdt, and Friedrich Glum. Their institutional touchstone was the Imperial Economic Council, as provided for by article 165 of the Weimar Constitution. This article envisioned a multi-level system of economic councils ranging from regional economic councils up to the Imperial Economic Council and involving representatives of all occupational groups in the performance of state tasks. However, only a Provisional Imperial Economic Council, with a restricted consultative remit, was ever actually established. Based on this model, Tatarin-Tarnheyden, Heinrich Herrfahrdt, and Friedrich Glum conceptualized organizational structures aiming at the comprehensive inclusion of non-state actors. They were legitimized primarily with reference to their output; that is, these organizational forms were supposed to enable a more appropriate and efficient realization of public interests. The input-based argument was basically a question of participation, which implies considerable proximity to typical topoi of democratic legitimation. This similarity is perhaps counter-intuitive, given that corporatist concepts are traditionally associated with anti-democratic ideologies due to their anti-parliamentarian slant. The numerous points of convergence between corporatist and democratic thought simultaneously reflect the heterogeneity of democratic reasoning in the Weimar period and the openness for ideas that were sceptical of—or even hostile to—parliamentary democracy and the party-based state.